Adaptive water resources planning to manage future risks to London's water supply - Murgatroyd, AL (2020)
Water resource management in the 21st Century is challenged by climate change impacts, increases in consumer demand, and environmental degradation. In the UK, water planners must secure long-term public water supply whilst facing increased exposure to climate-related hazards from increased aridity and uncertainties in future precipitation. It is widely accepted that to overcome such risks, water agencies must manage water demand, reduce the amount of water that is wasted through leakage, modify operational and regulatory policies, and build new supply infrastructure to increase water system capacity. However, significant uncertainties complicate adaptation decisions.